Negotiating Wage Settlements: A Structural Approach - Reshef, Yonatan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
While attracting a growing research attention, the wage determination process has largely been studied from an economic perspective. This study, in contrast, adopts a combined, economic and structural approach in an attempt to account for wage gains and concessions. This paper asks, which determinants, other than economic factors, may impact the outcomes of wage settlements? Given their economic and political environments, what are the choices available to parties pursuing the maximization of wage settlements? A logit analysis of 405 agreements filed with Alberta Labour, in 1987, shows that structural variables bear important impacts on the likelihood of wage negotiations to result in wage increases. This, in turn, carries important implications for union and management wage bargaining tactics which are also discussed.